PENGARUH HARGA, PROMOSI, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (STUDI PADA BENGKEL AHASS 0002 ASTRA MOTOR SILIWANGI SEMARANG) - Ade Oktafiara Saputra; Wahyu Hidayat (Universitas Diponegoro, 2017)
Astra Motor Siliwangi Semarang is an official dealer of Honda that has activity in selling products of Honda motorcycle and also serving the after-selling-service; such as repairing and spare parts selling. The objective of this study is to determine the effect of price, promotion, and service quality on customers satisfaction. This is an explanatory research. The method of collecting data is interview using quesioner. Samples consist of 100 respondents applied from purposive sampling technique. Data is analyzed using Linier Regression Test and Significance test is using SPSS 17.0. The result shows that 15.6% of price variable have positive effect on customers satisfaction parsially, 24.8% of promotion variable have positive effect on customers satisfaction parsially, and 41.5% of service quality variable have positive effect on customers satisfaction parsially. And simultantly 43,1% of price, promotion and service quality have positive effect on customers satisfaction. Based on the study result, therefore, it is suggested that Bengkel Ahass 0002 Astra Motor Siliwangi Semarang to maintain the price, increase the poducts promotion to customers. Maintaining the service quality consistency, keeping clean the bengkel area, and adding more facilities (Wi-Fi connection, books, snacks, and drinks) in order to make customers comfort while coming to the shop/bengkel.